Brazing & soldering - Cook, Jerome T.; Vaccari, John A.; Society of Manufacturing Engineers ([Dearborn, Mich.] : Society of Manufacturing Engineers, 2004)
Both brazing and soldering are common methods of joining metals, with uses in various industrial applications. This program covers the array of common brazing and soldering methods including torch brazing, batch furnace brazing, continous furnace brazing, dip brazing, induction brazing, iron soldering and wave soldering
Code no : DV03PUB124
Title from title screen
Executive producer, Steven R. Bollinger ; graphics by Jerome T. Cook, Dennis Summers, Quantum Dance Works ; video editing, Jim O'Donnell
Keywords: Solder and soldering -- Industrial applications; Brazing -- Industrial applications; Braze welding -- Industrial applications; Welded joints -- Industrial applications